Applications of Induced Pluripotent Stem Cells in Studying the Neurodegenerative Diseases - Wenbin Wan; Lan Cao; Bill Kalionis; Shijin Xia; Xiantao Tai (Stem Cells International)
Neurodegeneration is the umbrella term for the progressive loss of structure or function of neurons. Incurable neurodegenerative disorders such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) show dramatic rising trends particularly in the advanced age groups. However, the underlying mechanisms are not yet fully elucidated, and to date there are no biomarkers for early detection or effective treatments for the underlying causes of these diseases. Furthermore, due to species variation and differences between animal models (e.g., mouse transgenic and knockout models) of neurodegenerative diseases, substantial debate focuses on whether animal and cell culture disease models can correctly model the condition in human patients. In 2006, Yamanaka of Kyoto University first demonstrated a novel approach for the preparation of induced pluripotent stem cells (iPSCs), which displayed similar pluripotency potential to embryonic stem cells (ESCs). Currently, iPSCs studies are permeating many sectors of disease research. Patient sample-derived iPSCs can be used to construct patient-specific disease models to elucidate the pathogenic mechanisms of disease development and to test new therapeutic strategies. Accordingly, the present review will focus on recent progress in iPSC research in the modeling of neurodegenerative disorders and in the development of novel therapeutic options.